2003
DOI: 10.1080/14034940210165000
|View full text |Cite
|
Sign up to set email alerts
|

Progression to AIDS slowed even more after the first two years with highly active antiretroviral therapy

Abstract: The effectiveness of highly active antiretroviral treatment lasted for at least four and a half years and increased after the first two calendar years. The problem of less effectiveness among HIV-diagnosed intravenous drug users should be addressed by the health authorities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…These results agree with those of other authors [3,4,11,[17][18][19]. Compared with the period after 1996, the risk of death was more than ninefold for cases diagnosed up to 1990, and fourfold for the period 1991-1999, for both case definitions.…”
Section: Discussionsupporting
confidence: 92%
“…These results agree with those of other authors [3,4,11,[17][18][19]. Compared with the period after 1996, the risk of death was more than ninefold for cases diagnosed up to 1990, and fourfold for the period 1991-1999, for both case definitions.…”
Section: Discussionsupporting
confidence: 92%
“…The HIV/AIDS epidemic could still be looked upon as a relatively new epidemic with regard to the long infective period and the fact that the situation surrounding the epidemic is rapidly changing. The latest major change came with the introduction of HAART (highly active antiretroviral therapy) treatment in 1996, which seems to have significantly increased the survival times [4]. Still the continuous improvement of existing treatment, combined with the development of new treatment and perhaps future vaccines, creates great uncertainty about how the situation will be tomorrow or a year from now.…”
mentioning
confidence: 99%
“…Rates of disease progression, 0.0455, 0.125, 0.125, 0.25 infection known a 1 , a 2 , a 3 , a 4 HIV diagnosis rates 0.048, 0.048, 0.048, 0.132 infected individual gets aware of his disease, which hopefully results in a decreased risk behavior. A meta-analysis has concluded that those who knew their HIV-positive status altered their sexual risk practices [12].…”
mentioning
confidence: 99%